Research on Intelligent Optical Fiber Infrastructure Management Technology - Tao Zeng; Chengbin Shen; Ming Jiang (Dianxin kexue)
Along with the large scale of construction and operation of FTTx network,resource management of fiber infrastructure has become an important appeal point for operators.To meet the demand,internet of things technology was introduced to achieve automatic,intelligent fiber infrastructure management.Intelligent fiber infrastructure management technology based on electronic label,intelligent terminal,network management system,was studied.And then the progress of intelligent optical fiber infrastructure management system industry and standardization were investigated on account of some actual test results.Finally,application mode and development trends of intelligent fiber infrastructure management technology in the operator's network were analyzed.